A study of the relationship of an entrepreneur's age during his first business venture and success - Cristobal, Leenard; Loveres, Sara.; Ortega, Cherry; Pastelero, Michael; Tajanlangit, Verona Mae. (1998.)
The reasons for an entrepreneurs success remains to be one of the fascinating topics in management books. Some had attributed their success to their educational background, others to their attitude and still others to some economic socio-political background that they have. Indeed, to study those reason and discover some more in the process would be valuable for the entrepreneur aspirant. This research is another kind of those previous studies mentioned above only, its main focus lies between the relationship of the age of an entrepreneur when he put up a business to his success. Age here plays the determinant factor of the study. The researchers first selected randomly 51 respondents, each given a 3-page questionnaire which contains 25 questions. From the questionnaires, the findings of the study was gathered, tabulated and analyzed to arrive at a conclusion. At the end of the study, it was found out that starting a business at the age of 18-28 would mean an entrepreneur would become successful in terms of gain and location expansion than those belonging to ages 40-50. However, the paper cannot completely conclude that starting a business at an early age would make an entrepreneur successful because the data gathered is not sufficient to support such claim.
Research Paper (Mgt 199-Management Research). -- [Iloilo City] : University of the Philippines in the Visayas - College of Management, March 28, 1998.